2011
DOI: 10.1007/s00280-011-1749-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of curcumin oral absorption and pharmacokinetics of curcuminoids and curcumin metabolites in mice

Abstract: Purpose Curcumin has shown a variety of biological activity for various human diseases including cancer in preclinical setting. Its poor oral bioavailability poses significant pharmacological barriers to its clinical application. Here, we established a practical nano-emulsion curcumin (NEC) containing up to 20% curcumin (w/w) and conducted the pharmacokinetics of curcuminoids and curcumin metabolites in mice. Methods This high loading NEC was formulated based on the high solubility of curcumin in polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 34 publications
(45 reference statements)
7
86
0
2
Order By: Relevance
“…Dardano et al (2) also showed this increase of MN (about 3 fold) in control groups without any radioprotectors materials. They have proved a significant protective effect of Ginkgo biloba extract (GBE) in patients with Graves' disease and DTC receiving I-131 therapy for their treatments (2,32). The results of the present research also confirm that the administration of curcumin to the patients, at the current dose, was able to prevent the increase of MN about 34.2% compared with the control group.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Dardano et al (2) also showed this increase of MN (about 3 fold) in control groups without any radioprotectors materials. They have proved a significant protective effect of Ginkgo biloba extract (GBE) in patients with Graves' disease and DTC receiving I-131 therapy for their treatments (2,32). The results of the present research also confirm that the administration of curcumin to the patients, at the current dose, was able to prevent the increase of MN about 34.2% compared with the control group.…”
Section: Discussionsupporting
confidence: 76%
“…Curcumin showed a strong capacity to scavenging intracellular small oxidative molecules such as H 2 O 2 , HO, and ROO. There are no reports of toxicity of curcumin in oral administration (32,33). Curcumin plasma level range was from 29 to 419 ng/mL (33), and 22 to 42 ng/mL after 2 to 6 hours after single dose (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The poor transmembrane ability of Cur suspension may account for a limited and unsatisfactory inhibitory efficacy of Cur for IBD in clinical trials, which targeted preferentially intestinal epithelial cells rather than the deep focus (Lahiff & Moss, 2011). As previously reported, PEG could increase the transmembrane capacity of Cur through either chemical conjugation or physical suspension (Zhongfa et al, 2012). On the basis of prior release study, transmembrane Cur could probably exist in both free and conjugated forms.…”
Section: Transcellular Studiesmentioning
confidence: 88%